The Influence of Premiums, Claims and Profits on Risk Based Capital in Insurance Subsector Companies on the Indonesian Stock Exchange Period 2022-2023 - Herawati, Aty; Haikal, Muhammad (Dinasti Publisher, 2024)
The existence of the insurance company industry in Indonesia is considered very important by the government in overcoming the risks faced by society at any time. Because of this, the government imposes provisions for insurance companies regarding the financial health level requirements for insurance companies, namely by using Risk Based Capital. For insurance companies, premium income, claims and profits are important in the survival of insurance companies. The aim of this research is to determine the effect of premiums, claims and profits on Risk Based Capital. Research was conducted on insurance companies registered on the IDX in 2022-2023. The research sample consisted of 17 insurance companies for 2 years taken by purposive sampling with data completeness criteria during the research period. Data analysis was carried out using Panel Data Regression Analysis. The research results obtained are that there is a positive influence of Premiums on Risk Based Capital, there is a negative influence of Claims on Risk Based Capital and there is a negative influence of Profits on Risk Based Capital.